Cryogenic Engineering and Technologies Principles and Applications of Cryogen-Free Systems. - Zhao, Zuyu.; Wang, Chao. ([S.l.] : CRC PRESS, 2019)
Cryogen-free cryogenics is leading a revolution in research and industry by its significant advantages over traditional liquid helium systems. This is the first overview for the field, covering the key technologies, conceptual design, fabrication, operation, performance, and applications of these systems. The contents cover important topics such as the operating principles of 4K cryocoolers, enabling technologies (including vibration reduction) for cryogen free systems, the cryogen- free superconducting magnet, and cryogen-free systems that reach mK. It highlights the wide range of applications in materials science, quantum physics, astronomy and space science, medical sciences and etc. Key features: Introduce technologies and practical know-how employed for cryogen-free systems of using 4 K cryocoolers to replace liquid helium; Address state of the arts of cryogen-free superconducting magnets, sub-kelvin refrigeration systems of He-3 sorption cooler, adiabatic demagnetization refrigerator (ADR) and dilution refrigerators (DR). Discuss applications of cryogen-free systems in modern instruments and equipment.
OCLC-licensed vendor bibliographic record.
Keywords: Low temperature engineering; MEDICAL / Biotechnology; SCIENCE / Physics; SCIENCE / Solid State Physics